Breastfeeding Self Effi cacy and Effective Breastfeeding on Postpartum Mother - Retnayu Pradanie (Universitas Airlangga, 2015)
Introduction: Breastfeeding has been identifi ed as the optimal source of nutrition for infants. However, many mothers do not breastfeed their infants excusively. The possible modifi able factors to improve breastfeeding rates are breastfeeding self effi cacy and effective breastfeeding behavior. The aim of this study was to analyze the breastfeeding support package to improve breastfeeding self effi cacy and impact on effective breastfeeding behavior.Methods: This study was a quasy experiment pre-post test non equivalent control group design. Samples were 20 respondents recruited using consecutive sampling in Navy Hospital Dr. Ramelan who met the inclusion criteria. Instruments that used in this study were breastfeeding self effi cacy short form and LATCH assessment tool.Results: The score of breastfeeding self effi cacy on experiment group was improve higher than control group. But, the hypothesis test showed that there were no difference score between experiment and control group after intervention (p = 0.104). The correlation between breastfeeding self effi cacy and effective breastfeeding behavior was not signifi cant (p = 0.976). Conclusion: The antecedent of breastfeeding self effi cacy were not only the information resources but also job and education level. Breastfeeding self effi cacy was not an antecedent of effective breastfeeding behavior.